Multi-omics pan-cancer study of cuproptosis core gene FDX1 and its role in kidney renal clear cell carcinoma - Xu, Jiahao; Hu, Zhengang; Cao, Hui; Zhang, Hao; Luo, Peng; Zhang, Jian; Wang, Xiaoyan; Cheng, Quan; Li, Jingbo (Frontiers in Immunology, 2022)
Background: The mechanism of copper-induced cellular death was newly discovered and termed cuproptosis. Inducing cuprotosis in cancer cells is well expected for its curative potential in treating tumor diseases. However, Ferredoxin 1(FDX1), the core regulatory gene in cuprotosis is rarely studied and the regulation of FDX1 in tumor biology remains obscure. A comprehensive pan-cancer analysis of FDX1 is in need. Methods: 33 types of tumors were included with paired normal tissues in The Cancer Genome Atlas (TCGA) and The Genotype-Tissue Expression (GTEx) datasets. The interaction between transcription, protein, phosphorylation, and promoter methylation levels was analyzed. Survival analysis, immune infiltration, single-cell FDX1 expression, FDX1-related Tumor Mutant Burden (TMB), Microsatellite Instability (MSI), Stemness, Tumor Immune Dysfunction and Exclusion (TIDE), and immunotherapy-related analysis were analyzed. FDX1 protein expression was assessed by kidney renal clear cell carcinoma (KIRC) tissue microarray immunohistochemistry. The function of FDX1 in KIRC was further explored by experiments in 786-O cell lines in vitro. Results: FDX1 is highly expressed in 15 tumor types and lowly expressed in 11 tumor types. Corresponding changes in protein, phosphorylation, and promoter methylation level of FDX1 have been detected in several tumors. Survival analysis showed that FDX1 was related to favorable or poor overall survival in eight tumors and progression-free survival in nine tumors. Immune infiltration and single-cell analysis indicated the indispensable role of FDX1 expression in macrophages and monocyte. Established immunotherapy cohorts suggest FDX1 as a potential predictive gene. Further tissue microarray analysis and in vitro experiments in KIRC showed decreased FDX1 in KIRC patients and its silence could downregulate cuproptosis in kidney renal clear tumor cells. FDX1-associated gene expression signature in KIRC is related to the enrichment of genes involved in the TCA cycle, NOTCH pathway, etc. Several NOTCH pathway genes were differentially expressed in the high and low FDX1 groups in KIRC. Conclusion: Our analysis exhibited that FDX1 has differential expression and modification levels in various types of tumors, which is associated with cellular functions, immune modulation, and disease prognosis. FDX1 could be a brand-new cancer therapeutic target with the application of cuproptosis.